Greater Specificity of Sensorimotor Learning in the Elderly When Acquiring an Interceptive Task - Teixeira, Luis A.; Santos Lima, Elke dos (Current Aging Science, 2009)
In this investigation we assessed the extent to which young and elderly individuals become dependent on the specific visual situation present during practice of an interceptive task. Young and elderly participants practiced extensively a task of intercepting a virtually moving target under full vision or visual occlusion of the last 600 ms of target displacement. Before and after practice they were assessed in four visual conditions varying the time interval of visual display. The results showed that the elderly practicing under full vision had a progressive increase of temporal errors as a function of the period of visual occlusion after task acquisition. The elderly practicing under visual occlusion, conversely, achieved improved performance only in the visual condition experienced during task acquisition. Young individuals showed greater adaptability, presenting similar performance across visual conditions. Development of specific visuomotor integration only for the elderly seems to be related with the higher status that vision holds for movement control at this age.
Keywords: interception